2015
DOI: 10.1088/0957-4484/26/30/305602
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic molecule induced strong antiferromagnetic exchange coupling on a magnetic tunnel junction based molecular spintronics device

Abstract: This paper reports our Monte Carlo (MC) studies aiming to explain the experimentally observed paramagnetic molecule induced antiferromagnetic coupling between ferromagnetic (FM) electrodes. Recently developed magnetic tunnel junction based molecular spintronics devices (MTJMSDs) were prepared by chemically bonding the paramagnetic molecules between the FM electrodes along the tunnel junction's perimeter. These MTJMSDs exhibited molecule-induced strong antiferromagnetic coupling. We simulated the 3D atomic mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 35 publications
8
75
0
Order By: Relevance
“…However, we also noted that FMR response from the MTJ with Ta ( Fig. 5b) and without Ta on top [8] were very different. The further exploration about Ta role will be part of future study and beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…However, we also noted that FMR response from the MTJ with Ta ( Fig. 5b) and without Ta on top [8] were very different. The further exploration about Ta role will be part of future study and beyond the scope of this paper.…”
Section: Resultsmentioning
confidence: 69%
“…1i-k. The experimental details for SQUID magnetometer and FMR studies are discussed elsewhere [8]. SQUID study showed that the magnetic moment of the MTJ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 chemical structure. The exposed side edge of an MTJ was produced by the previously published liftoff based molecular device fabrication method 6,11 . In this study, the MTJ with Ta(5 nm)/Co(5-7 nm)/NiFe(5-3 nm)/AlOx(2 nm)/NiFe (10 nm) configuration was utilized.…”
mentioning
confidence: 99%